The View from DSQ - Brewer, Elizabeth; Brueggemann, Brenda Jo (Disability Studies Quarterly, 2014)
Analysis of publications in Disability Studies Quarterly between 2000-2012. Data and discussion concerning: the number of articles published; the number of articles collaboratively (or individually) authored; the kind and range of fields/disciplines that DSQ-published authors work in; the kind and range of methodologies generating DSQ-published research; the key terms for DSQ publications during this 13-year period (focusing both on titles and keywords). Conclusion summarizes trends and key points from the analysis and suggests a few points of further engagement for the future of Disability Studies. Keywords: Disability Studies Quarterly; methodologies; disciplines/fields; collaboration